In Situ IR‐ATR Study of the Interaction of Nitrogen Heteroaromatic Compounds with HY Zeolites: Experimental and Theoretical Approaches. Issue 4 (13th December 2019) - Khalil, Ibrahim; Celis‐Cornejo, Carlos M.; Thomas, Karine; Bazin, Philippe; Travert, Arnaud; Pérez‐Martínez, David J.; Baldovino‐Medrano, Víctor G.; Paul, Jean François; Maugé, Françoise
Abstract: In the present work, the liquid‐solid interaction of liquid N‐heteroaromatic compounds, commonly present in the petroleum feedstocks of the refineries, with Y zeolites used as hydrocracking catalysts was followed using IR‐ATR spectroscopy. The inhibition of the zeolitic acid sites by strongly basic pyridine and weakly basic indole was highlighted using a continuous flow IR‐ATR cell. Results were assessed by Density Functional Theory calculations to compute the vibrational frequencies of pyridine and indole according to the nature of the interaction sites: silanol groups or acidic OH groups. The study points out that IR‐ATR spectroscopy opens the way for investigating the interaction modes of low vapor pressure molecules (e. g. indole) that present an inherent difficulty to be operated in the gas phase. Moreover, the IR‐ATR makes possible the analysis of the little‐explored low wavenumber zone (<800 cm −1 ), that presents informative vibrational modes on the adsorption mode of N‐molecules. Hence, this work points out that for pyridine, the bands at 686 and 727 cm −1 are characteristic of pyridinium species formed over zeolitic OH groups, meanwhile, the signals at 703 and 750 cm −1, are associated to pyridine in interaction with silanol groups. The IR‐ATR study reveals that indole, a weakly basic compound, can be protonated on acidic Y zeolites as unambiguously evidenced by the formation of the bands at 1617, 1608, 1543 and 705 cm −1 . Findings here exposed are crucial for studying inhibitory effects exerted by weak nitrogenated compounds on acidic materials during hydrocracking processes. Abstract : Molecular modelling : The interaction modes leading to inhibit the hydrocracking catalysts (e. g. zeolites) by the weakly basic nitrogenates, such as indole, were not yet fully understood. The low vapor pressure of these molecules was presenting the inherent difficulty to their study in the gas phase setups. In this work we evidenced, by combining liquid‐solid IR‐ATR experiments with Density Functional Theory calculations, the vibrational frequencies of the different interaction modes of pyridine and indole with the zeolitic acid sites.